Discovery of the genus Vanhartenidia Lelej, 2006 (Hymenoptera: Mutillidae) in Egypt, with description of a new species - El-Torkey, Ashraf M.; Soliman, Ahmed M. (Zootaxa, 2015)
The genus Vanhartenidia Lelej, 2006 is newly recorded from Egypt. A new species, V. mandishaensis El-Torkey & Soliman, sp. nov. is described and illustrated from Bahariya Oasis (Giza, Egypt).